2011
DOI: 10.3892/etm.2011.252
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel molecular markers for detection of gastric cancer cells in the peripheral blood circulation using genome-wide microarray analysis

Abstract: Abstract.Although metastasis or relapse is a leading cause of death for patients with gastric cancer, the hematogenous spread of cancer cells remains undetected at the time of initial therapy. The development of novel diagnostic molecular marker(s) to detect circulating gastric cancer cells is an issue of great clinical importance. We obtained peripheral blood samples from 10 patients with gastric cancer who underwent laparotomy and 4 healthy volunteers. Microarray analysis consisting of 30,000 genes or ESTs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
0
21
0
3
Order By: Relevance
“…Although the overexpression of tetraspanin 8 has been described in relation to several human cancers [10][11][12][13], and it has been also reported that TSPAN8 mRNA is upregulated in the GC tissues compared to the normal gastric tissues by microarray analysis [14], the significance of tetraspanin 8 protein in GC remains unclear. Immunohistochemical analysis revealed that tetraspanin 8 protein was expressed in GC cells and that 72 (34 %) of 210 GC cases were positive for tetraspanin 8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the overexpression of tetraspanin 8 has been described in relation to several human cancers [10][11][12][13], and it has been also reported that TSPAN8 mRNA is upregulated in the GC tissues compared to the normal gastric tissues by microarray analysis [14], the significance of tetraspanin 8 protein in GC remains unclear. Immunohistochemical analysis revealed that tetraspanin 8 protein was expressed in GC cells and that 72 (34 %) of 210 GC cases were positive for tetraspanin 8.…”
Section: Discussionmentioning
confidence: 99%
“…Tetraspanins are involved in adhesion, motility, matrix modulation, and cell fusion [9]. Although it has been reported that TSPAN8 is expressed in the GC cell line [24], and that TSPAN8 mRNA is upregulated in GC tissues compared to normal gastric tissues according to microarray analysis [14], detailed expression of TSPAN8 has not been investigated. Among the 14 types of normal tissue, low-level TSPAN8 mRNA expression was detected in normal small intestine, colon, and liver.…”
Section: Generation Of the Mkn-45 Cast Librarymentioning
confidence: 99%
See 2 more Smart Citations
“…High-throughput cancer cell line screening provides a strategy to identify transcription markers to help guide targeted cancer therapy (38,39). Here, we present a computational strategy to profile unique transcriptional signatures associated with somatic mutations in combination with cancer lineage, using two metrics reflecting sensitivity and specificity independently.…”
Section: Discussionmentioning
confidence: 99%